Impact of cumulative steroid dose on infectious diseases after allogenic hematopoietic stem cell transplantation - Watanabe, Mizuki; Kanda, Junya; Hishizawa, Masakatsu; Kondo, Tadakazu; Yamashita, Kouhei; Takaori‐Kondo, Akifumi (Transplant Infectious Disease, 2019)
Background Systemic steroid is used to treat various transplant‐related complications after allogenic hematopoietic stem cell transplantation (allo‐HSCT). However, measures to evaluate its impact on infections are still limited. Hence, we examined the cumulative steroid dose used within 30 days after transplant as a predictor of future risk of infections. Methods This study included 226 patients who underwent their first allo‐HSCT at Kyoto University Hospital between 2005 and 2015. Results Sixty‐one patients received transplantation from related donors, 106 received unrelated BMT and 59 received unrelated single‐unit CBT. Patients were categorized into three groups according to the cumulative steroid dose in terms of prednisolone: no‐steroid group (n = 174), low‐dose group (≤7 mg/kg) (n = 22) and high‐dose group (>7 mg/kg) (n = 30). In a multivariate analysis, high‐dose steroid administration was associated with cytomegalovirus (CMV) antigenemia (HR 1.91, P = 0.037) and bacteremia (HR 2.59, P = 0.053). No impact was found on the occurrence of invasive fungal infection. Conclusion High‐dose cumulative steroid could predict high risks of bacteremia and CMV antigenemia. Additional anti‐bacterial agents for fever and regular measurement of CMV antigen are recommended for whom with systemic steroid administration even after neutrophil engraftment.